Lynch syndrome–associated urothelial carcinoma: clinical and molecular findings from a single-institution cohort - A. Rametta; M. Barella; A. Scardino; F. Barbetta; E. Tamborini; F. Perrone; A. Busico; L. Agnelli; S. Rota; E. Gusmaroli; M. Stellato; A. Nuzzo; et al. (Familial Cancer, 2026)

Soil health indicator variability and management sensitivity across soils, bioregions, and agricultural systems - Katherine A. Dynarski; Ekundayo Adeleke; R. Louis Baumhardt; Joseph Burke; Tiffany Carter; Paul DeLaune; Huijie Gan; Julie Grossman; Josh Heitman; Divya Kandanool; Katie Lewis; Katherine Naasko; et al. (Agriculture, Ecosystems & Environment, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

In Response to “Comment on Ensuring the Efficacy and Safety of Approved Medications” - Maryann Mazer-Amirshahi; Jon B. Cole; Andrew I. Stolbach; Jeanmarie Perrone; Lewis S. Nelson (Journal of Medical Toxicology, 2024)

Ensuring the Efficacy and Safety of Approved Medications - Maryann Mazer-Amirshahi; Jon B. Cole; Andrew I. Stolbach; Jeanmarie Perrone; Lewis S. Nelson (Journal of Medical Toxicology, 2024)

Integrated geophysical and geological surveys reveal new details of the large Montescaglioso (southern Italy) landslide of December 2013 - G. Calamita; M.R. Gallipoli; E. Gueguen; R. Sinisi; V. Summa; L. Vignola; T.A. Stabile; J. Bellanova; S. Piscitelli; A. Perrone (Engineering Geology, 2023)

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

The Impact of the Parenteral Opioid Medication Shortages on Opioid Utilization Practices in the Emergency Department of Two University Hospitals - Amanda J. Deutsch; David A. Gajdosik; Christine Ramdin; Collin Tebo; Maryann Mazer-Amirshahi; Erin R. Fox; Josh Colorado; Lewis S. Nelson; Jeanmarie Perrone (Journal of Medical Toxicology, 2021)

Opioid Overdose Deaths with Buprenorphine Detected in Postmortem Toxicology: a Retrospective Analysis - Rachel S. Wightman; Jeanmarie Perrone; Rachel Scagos; Maxwell Krieger; Lewis S. Nelson; Brandon D.L. Marshall (Journal of Medical Toxicology, 2021)

Physical stratigraphy and geotechnical properties controlling the local seismic response in explosive volcanic settings: the Stracciacappa maar (central Italy) - M. Moscatelli; G. Vignaroli; A. Pagliaroli; R. Razzano; A. Avalle; I. Gaudiosi; S. Giallini; M. Mancini; M. Simionato; P. Sirianni; G. Sottili; J. Bellanova; et al. (Bulletin of Engineering Geology and the Environment, 2021)
Nowadays, policies addressed to prevention and mitigation of seismic risk need a consolidated methodology finalised to the assessment of local seismic response in explosive volcanic settings. The quantitative reconstruction of the subsoil model provides a key instrument to understand how the geometry and the internal architecture of outcropping and buried geological units have influence on the propagation of seismic waves. On this regard, we present a multidisciplinary approach in the test area of the Stracciacappa maar (Sabatini Volcanic District, central Italy), with the aim to reconstruct its physical stratigraphy and to discuss how subsoil heterogeneities control the 1D and 2D local seismic response in such a volcanic setting. We first introduce a new multidisciplinary dataset, including geological (fieldwork and log from a 45-m-thick continuous coring borehole), geophysical (electrical resistivity tomographies, single station noise measurements, and 2D passive seismic arrays), and geotechnical (simple shear tests performed on undisturbed samples) approaches. Then, we reconstruct the subsoil model for the Stracciacappa maar in terms of vertical setting and distribution of its mechanical lithotypes, which we investigate for 1D and 2D finite element site response analyses through the application of two different seismic scenarios: a volcanic event and a tectonic event. The numerical modelling documents a significant ground motion amplification (in the 1–1.5 Hz range) revealed for both seismic scenarios, with a maximum within the centre of the maar. The ground motion amplification is related to both 1D and 2D phenomena including lithological heterogeneity within the upper part of the maar section and interaction of direct S-waves with Rayleigh waves generated at edges of the most superficial lithotypes. Finally, we use these insights to associate the expected distribution of ground motion amplification with the physical stratigraphy of an explosive volcanic setting, with insights for seismic microzonation studies and local seismic response assessment in populated environments.

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

Buprenorphine Initiation in the Emergency Department: a Thematic Content Analysis of a #firesidetox Tweetchat - Megan Chenworth; Jeanmarie Perrone; Jennifer S. Love; Howard A. Greller; Abeed Sarker; Peter R. Chai (Journal of Medical Toxicology, 2020)

Leadership Roles in Opioid Stewardship and the Treatment of Patients with Opioid Use Disorder Among Medical Toxicologists - Joseph E. Carpenter; Brian Patrick Murray; Maryann Mazer-Amirshahi; JoAn R. Laes; Nicholas Nacca; Lewis S. Nelson; Jeanmarie Perrone; Evan S. Schwarz; Timothy J. Wiegand; Paul M. Wax (Journal of Medical Toxicology, 2020)

The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

ACMT Position Statement: Remove the Waiver Requirement for Prescribing Buprenorphine for Opioid Use Disorder - Ryan Marino; Jeanmarie Perrone; Lewis S. Nelson; Timothy J. Wiegand; Evan S. Schwarz; Paul M. Wax; Andrew I. Stolbach (Journal of Medical Toxicology, 2019)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Removal of methylparaben from synthetic aqueous solutions using polyacrylonitrile beads: kinetic and equilibrium studies - Maurizio Forte; Luigi Mita; Rosa Perrone; Sergio Rossi; Mario Argirò; Damiano Gustavo Mita; Marco Guida; Marianna Portaccio; Tzonka Godievargova; Yavour Ivanov; Mahmoud T. Tamer; Ahmed M. Omer; et al. (Environmental Science and Pollution Research, 2017)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Impact of desert dust events on short- and long-wave radiation at the surface over south-eastern Italy - S. Romano; M. R. Perrone (Arabian Journal of Geosciences, 2016)

Columnar and ground-level aerosol optical properties: sensitivity to the transboundary pollution, daily and weekly patterns, and relationships - M. R. Perrone; S. Romano; J. A. G. Orza (Environmental Science and Pollution Research, 2015)

Bridge-Enhanced ACL Repair: A Review of the Science and the Pathway Through FDA Investigational Device Approval - Benedikt L. Proffen; Gabriel S. Perrone; Gordon Roberts; Martha M. Murray (Annals of Biomedical Engineering, 2015)

Prevalence of respiratory colonisations and related antibiotic resistances among paediatric tracheostomised patients of a long-term rehabilitation centre in Italy - M. Pozzi; P. Pellegrino; S. Galbiati; M. Granziera; F. Locatelli; C. Carnovale; V. Perrone; S. Antoniazzi; C. Perrotta; S. Strazzer; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Lipid interactions of LAH4, a peptide with antimicrobial and nucleic acid transfection activities - Barbara Perrone; Andrew J. Miles; Evgeniy S. Salnikov; B. A. Wallace; Burkhard Bechinger (European Biophysics Journal, 2014)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Assuring Safety of Inherently Unsafe Medications: the FDA Risk Evaluation and Mitigation Strategies - Lewis S. Nelson; Meredith Loh; Jeanmarie Perrone (Journal of Medical Toxicology, 2014)

From Bench to Humans: Formulation Development of a Poorly Water Soluble Drug to Mitigate Food Effect - Preetanshu Pandey; Rhye Hamey; Dilbir S. Bindra; Zongyun Huang; Neil Mathias; Timothy Eley; John Crison; Brian Yan; Robert Perrone; Chandra Vemavarapu (AAPS PharmSciTech, 2014)

Electronic Pharmacopoeia: A Missed Opportunity for Safe Opioid Prescribing Information? - Jeff Lapoint; Jeanmarie Perrone; Lewis S. Nelson (Journal of Medical Toxicology, 2014)

Prescribing Practices, Knowledge, and Use of Prescription Drug Monitoring Programs (PDMP) by a National Sample of Medical Toxicologists, 2012 - Jeanmarie Perrone; Francis J. DeRoos; Lewis S. Nelson (Journal of Medical Toxicology, 2012)

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility - G. V. F. Brunoro; E. V. Wolfgramm; I. D. Louro; I. I. Degasperi; V. C. W. Busatto; A. M. S. Perrone; M. C. P. Batitucci (Molecular Biology Reports, 2011)

Post-collisional tectonics in the Northern Cottian Alps (Italian Western Alps) - G. Perrone; P. Cadoppi; S. Tallone; G. Balestro (International Journal of Earth Sciences, 2011)

Pharmacy and Therapeutics Committees: Leadership Opportunities in Medication Safety for Medical Toxicologists - Jeanmarie Perrone; Lewis S. Nelson (Journal of Medical Toxicology, 2011)

Coronary computerized tomography angiography for rapid discharge of low-risk patients with cocaine-associated chest pain - Kristy M. Walsh; Anna Marie Chang; Jeanmarie Perrone; Christine M. McCusker; Frances S. Shofer; Mark J. Collin; Harold I. Litt; Judd E. Hollander (Journal of Medical Toxicology, 2009)

Neonatal pain analyzer: development and validation - R. Sisto; C. V. Bellieni; S. Perrone; G. Buonocore (Medical & Biological Engineering & Computing, 2006)